Legal Assistance by Advocates in Gender Mainstreaming: A Reflection - Anak Agung Sagung Laksmi Dewi (Fakultas Hukum, Universitas Warmadewa, 2022)
Gender mainstreaming has become one of the legal politics in Indonesia, this is in line with the nature contained in Law Number 17 of 2007 concerning National Long-Term Development of 2005-2025. Therefore, gender mainstreaming needs special attention in some of its supporting elements. One of the supporting elements is legal aid, as a form of preventive and repressive efforts in realizing gender equality in responding to discrimination that is often experienced by women in Indonesia. one of the supporters of these preventive and repressive efforts is legal aid which can normatively be carried out by advocates in Indonesia. This should be a common thread in the protection of women's rights and gender mainstreaming in Indonesia which is carried out through legal aid in Indonesia. When scrutinized again in the regulation regarding the concept of legal aid as stated in Law Number 18 of 2003 concerning Advocates and Law Number 16 of 2011 concerning Legal Aid, legal aid can only be given to â€œpoor or incapable peopleâ€. Meanwhile, women are one of the people who are often in a cornered/unfavorable/marginalized position in physical, opportunity and social status. So that it becomes an urgent condition to expand the interpretation of â€œpoor or incapable peopleâ€ so that legal aid that is the obligation of advocates or legal aid providers can also include assistance to women in an effort to realize gender mainstreaming in Indonesia.